Materiality in Transition: Challenges and Opportunities in Corporate Sustainability Reporting under the CSRD - Måns Dunfjäll (European Journal of Risk Regulation)
This article examines the concept of materiality in sustainability reporting, tracing its development from financial materiality to the adoption of double materiality under the Corporate Sustainability Reporting Directive (CSRD). It explores the distinction between financial and impact materiality, highlighting the regulatory and ideological shifts that have shaped their integration. The discussion also includes the challenges companies face in implementing double materiality, such as data collection complexities, methodological inconsistencies, and the risks of selective disclosure. Additionally, the article contains an analysis of potential solutions, including additional regulatory guidance, independent oversight, and best practices for balancing transparency with strategic reporting. Ultimately, the author argues that double materiality represents a significant transformation in corporate governance, and that there exists concrete measures to be taken by both companies and regulators to improve the application of the CSRD.